O trabalho de campo no ensino de Geografia: a cidade como experiência educativa - Bachelli, Davi [UNIFESP] (2019)
In this study we aimed at investigating the contribution of the methodology of the field work in the teaching of Geography and its relevance in the study of the city. We understand the city as a result of human work, that is, as the materialization of the complexity of human relations in the geographical space, in this case the urban space. Some authors (CASTELLAR, 2010 and CAVALCANTI, 2008) suggest that it is possible for students to understand the city from the perspective of experience, that is, from their personal experiences or, also, to reproduce statements conveyed in the media. It is common, for instance, that in this perspective the problems experienced by people in their daily lives, such as traffic, violence, homelessness, infrastructure issues, among others, are considered. For geographic learning it is important to consider the individual's experience with the city, but it is necessary to move beyond the lived space. In order for a meaningful learning to take place (AUBUBEL, 2006), the student must relate some concepts such as time and space, local and global, as well as having ideas for solving problems, developing their autonomy and positioning themselves critically, that is, develop new skills for understanding and applying scientific concepts. Because of this complexity, the methodology of fieldwork in the study of the city can become an ally in the process of teaching and learning of Geography, re-signifying the relationship of the individual with the city and making personal experience with this space a positive educational experience (DEWEY, 2011).